Integration of the Spiritual Emotional Freedom Technique (SEFT) Model and the Concept of Tazkiyatun Nafs from Imam Ghazali's Perspective for the Recovery Process of Clients with Psychological Disorders - Eva Nur Hopipah; Iik Arifin Mansurnoor; Yusuf Rahman (Journal of Islamic Communication and Counseling, 2025)
Psychological issues such as stress, anxiety, and depression are becoming more common in today's world. Many traditional therapies focus only on mental and emotional aspects, while often ignoring spiritual dimensions. In Islam, the concept of Tazkiyatun Nafs by Imam Al-Ghazali emphasizes the purification of the soul to help individuals control desires and improve their character. At the same time, the Spiritual Emotional Freedom Technique (SEFT) is known as a spiritual-based therapy that helps reduce emotional problems. This study aims to create a more comprehensive healing model by integrating the Spiritual Emotional Freedom Technique (SEFT) with the concept of Tazkiyatun Nafs. It explores how this combination may reduce psychological symptoms. The findings are expected to serve as a theoretical foundation for the future development of intervention models aligned with Islamic psychotherapy approaches. The method used is library research, where relevant books and sources are analyzed. A descriptive-comparative approach is used to compare the key ideas between SEFT and Tazkiyatun Nafs, and to explore their connections. The results suggest that this integration provides a helpful and balanced approach. SEFT works through prayer and tapping techniques, while Tazkiyatun Nafs offers spiritual stages such as self-cleansing (takhalli), self-development (tahalli), and self-realization (tajalli). Core values ​​such as sincerity, mindfulness, surrender, and gratitude support this process, helping individuals heal emotionally and grow spiritually.